Realization of modified Luneburg lens antenna using quasi‐conformal transformation optics and additive manufacturing. Issue 4 (28th December 2018) - Biswas, Soumitra; Lu, Aric; Larimore, Zachary; Parsons, Paul; Good, Austin; Hudak, Nicholas; Garrett, Benjamin; Suarez, John; Mirotznik, Mark S.
Abstract: We demonstrate a new method for realizing modified Luneburg lens antennas with nearly continuously graded permittivity profiles in three‐dimensions. The method used a quasi‐conformal transformation optics (QCTO) approach to modify the geometry and permittivity of a spherical Luneburg lens to have a flat surface for convenient integration of antenna feeds. The modified lens was then fabricated using Fused Deposition Modeling (FDM) printing with an effective media approach that employs space‐filling curves. The method was validated by designing and fabricating a modified Luneburg lens antenna designed to operate in the Ka‐band. The antenna performance of the sample was measured experimentally and shown to compare well to predicted results using full wave simulations. The device was able to achieve a reasonably high degree of beam steering (ie, −55° to +55°) over the entire Ka‐band. We believe this new approach provides a cost‐effective and scalable means of realizing practical passive beam steering lenses that operate over a broad range of frequencies.